Optimalkan Pembelajaran Biologi: Peran Interaksi Keterampilan Berpikir Kritis dan Argumentasi terhadap Self Efficacy Mahasiswa - Indah Kencanawati; Toni Haryanto; Nurhasnah Nurhasnah (Symbiotic: Journal of Biological Education and Science, 2023)
Critical thinking and argumentation skills play an important role in influencing students' level of self-efficacy in the biology learning process. The research approach used in this study is a quantitative method with a 2 x 2 factorial design. Data were analyzed using SPSS software to present descriptive statistics of critical thinking skills with arguments on self-efficacy, as well as testing the inter-subject effects of critical thinking skills with arguments on self-efficacy. The research results indicate that there is a significant difference between critical thinking skills and argumentation in influencing the level of self-efficacy. Therefore, it can be concluded that the null hypothesis (Ho) which states that there is no interaction between critical thinking skills and argumentation in influencing self-efficacy, is rejected. The research conclusion confirms that there is a significant interaction between critical thinking skills and argumentation in influencing self-efficacy. This interaction follows an ordinal relationship pattern which is depicted almost at the intersection of the lines between the high and low groups, indicating the influence of critical thinking skills and argumentation on self-efficacy.